On the German Monetary Transmission Mechanism: Interest Rate and Credit Channels for Investment Spending - Robert S. Chirinko; Ulf von Kalckreuth (Center for Economic Studies and ifo Institute (CESifo), 2003)
The transmission channels through which monetary policy affects business investment remain opaque. This paper examines the importance of the interest rate and credit channels on business fixed investment in Germany. We have at our disposal three uniquely rich datasets - a panel of financial statement data for 6,408 firms (44,345 datapoints) supplemented with user costs of capital and confidential measures of creditworthiness. We uncover a statistically significant interest rate channel. Its economic significance can be sizeable, but depends on auxiliary assumptions. Sorting firms with our direct measure of creditworthiness, we find that credit constraints are important for a subset of firms. Sortings by firm size or dividend payout ratios shed some light on continuing debates in the literature.
Keywords: E22; E50; 330